Annual assessment of highway traffic noise using two channel short-term measurements - Jagniatinskis, Aleksandras; Fiks, Boris; Dimitriu, Delia (Transport, 2014)
Research has shown that for residential area nearby (up to 50 m) exurbia roads, there are cases where the evaluation of noise impact needs more than using the calculation methods alone. Thus, in order to confirm (or not) the implementation of designed measures for noise abatement procedures in these areas, some direct acoustical measurements of traffic flow are required. The present paper deals with the development of new approach to the methodology that allows truly estimate the annual Lden value using the one short-term (till 1 h) time interval measurement. The method is based on the original extrapolation procedure that allows to adapt results obtained in representative shortterm time interval to the annual average rating time periods of day (12 h), evening (4 h) and night (8 h), for which the Lden value is assessed. The procedure is based on the statistical processing of Sound Exposure Levels (SEL) distribution histogram of all vehicles passing by and registered on the reference microphone. The sound propagation correction is evaluated by applying simultaneous measured sound levels registration on two microphones, placed in reference point and in receiver point, considering living environment. This method allows to extend results of extrapolation obtained in the reference point into desired environment point, where such extrapolation to the annual noise levels can not be done.